Introduction to the special focus issue on the impact of diet on gut microbiota composition and function and future opportunities for nutritional modulation of the gut microbiome to improve human health. (4th March 2017) - Donovan, Sharon M.
ABSTRACT: Over the past decade, application of culture-independent, next generation DNA sequencing has dramatically enhanced our understanding of the composition of the gut microbiome and its association with human states of health and disease. Host genetics, age, and environmental factors such as where and who you live with, use of pre-, pro- and antibiotics, exercise and diet influence the short- and long-term composition of the microbiome. Dietary intake is a key determinant of microbiome composition and diversity and studies to date have linked long-term dietary patterns as well as short-term dietary interventions to the composition and diversity of the gut microbiome. The goal of this special focus issue was to review the role of diet in regulating the composition and function of the gut microbiota across the lifespan, from pregnancy to old age. Overall dietary patterns, as well as perturbations such as undernutrition and obesity, as well as the effects of dietary fiber/prebiotics and fat composition are explored.